2010
DOI: 10.1042/bsr20090163
|View full text |Cite
|
Sign up to set email alerts
|

Overexpression of xCT induces up-regulation of 14-3-3β in Kaposi's sarcoma

Abstract: KSHV (Kaposi's sarcoma-associated herpesvirus), or HHV-8 (human herpesvirus 8), is associated with the pathogenesis of KS, the most common AIDS-related malignancy. xCT (functional subunit of the cystine/glutamate transporter xc− system) is known as the HHV-8 fusion-entry receptor as well as an oncogenic protein. How the xCT triggers the signal transduction of HHV-8 infection and the cell proliferation remains incomplete. We found that xCT was overexpressed in KS tissues and HHV-8-positive BCBL-1 cells. When xC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
12
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 21 publications
1
12
0
Order By: Relevance
“…Our data are consistent with published data indicating that the upregulation of xCT by miR-K12-11 results in xCT-mediated activation of 14-3-3␤ expression, which, in turn, leads to 14-3-3␤-mediated transcriptional repression of DUSP1 (32,33,51,53,54). For additional confirmation, we show that targeting 14-3-3␤ restores DUSP1 expression and reduces the production of promigratory factors and endothelial cell invasiveness under conditions of either KSHV infection or ectopic miR-K12-11 expression.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…Our data are consistent with published data indicating that the upregulation of xCT by miR-K12-11 results in xCT-mediated activation of 14-3-3␤ expression, which, in turn, leads to 14-3-3␤-mediated transcriptional repression of DUSP1 (32,33,51,53,54). For additional confirmation, we show that targeting 14-3-3␤ restores DUSP1 expression and reduces the production of promigratory factors and endothelial cell invasiveness under conditions of either KSHV infection or ectopic miR-K12-11 expression.…”
Section: Discussionsupporting
confidence: 82%
“…Existing data suggest that the 14-3-3␤/14-3-3␤ interactant 1 (FBI1) complex binds the promoter region of DUSP1 and acts as a transcriptional repressor, thereby increasing ERK activation and promoting anchorage-independent growth, tumorigenicity, and metastasis (51). One study also reported that overexpression of the amino acid transporter xCT (a fusion/entry receptor for KSHV [52]) induces upregulation of 14-3-3␤ expression in KSHV-infected cells through mechanisms not yet defined (53). We have reported previously that KSHV-encoded miR-K12-11 upregulates xCT expression through repression of BACH-1, a negative transcriptional regulator of xCT (32), and others have confirmed that miR-K12-11 targets the BACH-1 3= UTR (33,54).…”
Section: Mir-k12-11 Induces Endothelial Cell Invasion Through Indirecmentioning
confidence: 99%
“…Latent protein LANA-2, detected exclusively in KSHV-infected B cells, has been shown to interact with 14-3-3 proteins and inhibit FOXO3␣ transcription factor (80). In another study, overexpression of xCT, an HHV-8 fusion-entry receptor, was shown to induce upregulation of 14-3-3␤ in KS (118). LANA-1 could interact with 14-3-3 in endothelial cells to function either in ways similar to those of LANA-2 or via a different mechanism to prevent cell cycle arrest.…”
Section: Discussionmentioning
confidence: 94%
“…Upregulation of 14-3-3β promoted cell proliferation and tumor formation by the mitogen-activated protein kinase (MAPK)-dependent signaling pathway in NIH3T3 cells (39). Increased expression of 14-3-3β was observed in Kaposi's sarcoma and papillary thyroid carcinomas and promoted cell proliferation and tumor progression (41,42). Our previous studies demonstrated that 14-3-3β expression increased with the degree of human astrocytoma.…”
Section: Discussionmentioning
confidence: 99%
“…14-3-3β is expressed in tumor tissues and cell lines of many types of cancers including lung, prostate and breast cancer (42,43). However, the mechanism of 14-3-3β in the regulation of cancer cells is quite complicated.…”
Section: Discussionmentioning
confidence: 99%